Reduplikasi dalam Novel Rintik Terakhir Karya Sir Puji Hartini serta Implikasinya dalam Pembelajaraan Bahasa Indonesia di SMK - Regian Sini; Linggua Sanjaya Usop; Misnawati Misnawati; Yuliati Eka Asi; Paul Diman; Nirena Ade Christy; Syarah Veniaty; Yulina Mingvianita; Ibnu Yustiya Ramadhan; Stefani Ratu Lestariningtyas1 (Universitas Palangka Raya, 2025)
The purpose of this study is to describe (1) the types of reduplication in the novel Rintik Terakhir by Sri Puji Hartini, (2) the meaning of reduplication in the novel Rintik Terakhir by Sri Puji Hartini, (3) its implications for learning Indonesian in vocational schools. The study uses a qualitative approach with a type of data analysis technique. The data source in this study is the novel Rintik Terakhir by Sri Puji Hartini. The data in it are types of reduplication and the meaning of reduplication. The results of this study indicate the use of types of reduplication and the meaning of reduplication in the novel Rintik Terakhir by Sri Puji Hartini. The types of reduplication refer to pure reduplication (14 data), sound change reduplication (8 data) and affixed reduplication (19 data) found in the novel. The meaning of reduplication refers to the reduplication of noun repetition in the form of variation/many reduplication (8 data), reduplication of verb repetition in the form of reduplication stating repeated work (4 data), and reduplication of adjective repetition in the form of intensity reduplication (3 data). This research is implied in learning Indonesian in SMK.